2020
DOI: 10.3389/fonc.2020.589434
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Lactic Acidosis: Protecting Tumor by Inhibiting Cytotoxic Activity Through Motility Arrest and Bioenergetic Silencing

Abstract: Adoptive T cell therapy (ACT) is highly effective in the treatment of hematologic malignancies, but shows limited success in solid tumors. Inactivation of T cells in the tumor milieu is a major hurdle to a wider application of ACT. Cytotoxicity is the most relevant activity for tumor eradication. Here, we document that cytotoxic T cells (CTL) in lactic acidosis exhibited strongly reduced tumor cell killing, which could be compensated partly by increasing the CTL to tumor cell ratio. Lactic acid intervened at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…In our studies, 12.5-mM lactic acid suppressed cytokine production and reduced the pH of the buffered media to 6.7 . It remained significantly lower than control media for 1 h. Fischbeck et al (2020) observed a similar drop in pH with 10-mM lactic acid and a drop to pH 6.3 with 20-mM lactic acid addition. Additionally, we observed that formic acid, with a similar pKa, also suppressed IL-6 secretion, and sodium lactate above 20 mM could mimic lactic acid.…”
Section: Discussion Of Cell-specific Effectsmentioning
confidence: 52%
See 3 more Smart Citations
“…In our studies, 12.5-mM lactic acid suppressed cytokine production and reduced the pH of the buffered media to 6.7 . It remained significantly lower than control media for 1 h. Fischbeck et al (2020) observed a similar drop in pH with 10-mM lactic acid and a drop to pH 6.3 with 20-mM lactic acid addition. Additionally, we observed that formic acid, with a similar pKa, also suppressed IL-6 secretion, and sodium lactate above 20 mM could mimic lactic acid.…”
Section: Discussion Of Cell-specific Effectsmentioning
confidence: 52%
“…Lactate and the associated H + ions have similar inhibitory effects on glycolysis in immune cells ( Figure 1 ). Lactic acid, which rapidly dissociates to lactate and H + , suppressed glycolysis in the myeloid lineage and T cells, as measured by Seahorse metabolic flux analysis ( Dietl et al, 2010 ; Errea et al, 2016 ; Ratter et al, 2018 ; Fischbeck et al, 2020 ; Quinn et al, 2020 ). Lactic acid suppressed glucose uptake, lactate export, glycolytic enzyme expression, and intracellular ATP levels in monocytes and mast cells ( Dietl et al, 2010 ; Caslin et al, 2019 ).…”
Section: Receptor Transport and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, under sub-optimal perfusion, glycolytic co-option produces a highly acidic environment that suppresses T-cell effector functions 8 . Additionally, angiogenic tumor endothelial cells express death signals like FAS ligand (FASLG) that induce apoptosis in infiltrating cytotoxic T-cells 9 .…”
mentioning
confidence: 99%